2017
DOI: 10.1177/0144598717709667
|View full text |Cite
|
Sign up to set email alerts
|

Multiple controlling factors of lower Palaeozoic organic-rich marine shales in the Sichuan Basin, China: Evidence from minerals and trace elements

Abstract: Lower Palaeozoic organic-rich shales are widely distributed in southern China. In this study, the organic matter contents of Lower Cambrian, Upper Ordovician, and Lower Silurian shales were analysed, and a high degree of vertical heterogeneity was found. In the studied sections, the total organic carbon concentrations are high at the bottom and gradually decrease upward. The total sulphur contents of the studied shales display a similar trend in the vertical direction, and they are high in the lower part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…All the evidence discussed here, combined with reported hydrothermal sedimentary phenomenon in the Longmaxi Formation shale (Wu et al, 2017;Zhang et al, 2018), indicates that hydrothermal intrusion might have occurred during the deposition of the LLF in the Sichuan Basin, and the impact of these hydrothermal fluids varied in different regions at different periods. The geochemical indexes of hydrothermal activity (Fe, Mn, and Y concentrations and Fe/Ti ratio) indicated that the LLF in the Weiyuan area was more affected by hydrothermal activity than the LLF in the Jiaoshiba and Zhaotong areas.…”
Section: Hydrothermal Activitysupporting
confidence: 52%
See 3 more Smart Citations
“…All the evidence discussed here, combined with reported hydrothermal sedimentary phenomenon in the Longmaxi Formation shale (Wu et al, 2017;Zhang et al, 2018), indicates that hydrothermal intrusion might have occurred during the deposition of the LLF in the Sichuan Basin, and the impact of these hydrothermal fluids varied in different regions at different periods. The geochemical indexes of hydrothermal activity (Fe, Mn, and Y concentrations and Fe/Ti ratio) indicated that the LLF in the Weiyuan area was more affected by hydrothermal activity than the LLF in the Jiaoshiba and Zhaotong areas.…”
Section: Hydrothermal Activitysupporting
confidence: 52%
“…Co is considered to be associated with a common seawater source, while Zn and Ni are primarily considered to be from hydrothermal origins. Therefore, a Ni-Zn-Co ternary diagram was established and is used to distinguish hydrogenic and hydrothermal sediments (Choi and Hariya, 1992;Wu et al, 2017). Fig.…”
Section: Hydrothermal Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The anomaly of uranium, or the so-called uranium coefficient, depends on the relationship between uranium and thorium to determine the redox environment. To determine the anomaly coefficient, the following equation (Wignall, 1994 in Wu et al, 2017) is used:…”
Section: Geochemistry: Geochemical Proxies For Oxygen Abundance Condi...mentioning
confidence: 99%